The usefulness of fungicide mixtures and alternation for delaying the selection for resistance in populations of mycosphaerella graminicola on winter wheat: A modeling analysis - Hobbelen, P.; Paveley, N.; Oliver, Richard; van den Bosch, F. (American Phytopathological Society, 2013)
A fungicide resistance model (reported and tested previously) was amended to describe the development of resistance in Mycosphaerella graminicola populations in winter wheat (Triticum aestivum) crops in two sets of fields, connected by spore dispersal. The model was used to evaluate the usefulness of concurrent, alternating, or mixture use of two high-resistance-risk fungicides as resistance management strategies. We determined the effect on the usefulness of each strategy of (i) fitness costs of resistance, (ii) partial resistance to fungicides, (iii) differences in the dose-response curves and decay rates between fungicides, and (iv) different frequencies of the double-resistant strain at the start of a treatment strategy. Parameter values for the quinine outside inhibitor pyraclostrobin were used to represent two fungicides with differing modes of action. The effectiveness of each strategy was quantified as the maximum number of growing seasons that disease was effectively controlled in both sets of fields. For all scenarios, the maximum effective lives achieved by the use of the strategies were in the order mixtures ≥ alternation ≥ concurrent use. Mixtures were of particular benefit where the pathogen strain resistant to both modes of action incurred a fitness penalty or was present at a low initial frequency.